A Numerical Experiment of Full Waveform Inversion of Complex Structures Concealed Around a Horizontal Hydraulic Fracturing Well Using Perforation Seismic Data - Qian, Guang; Yu, Jiashun; Yuan, Jianlong; Fu, Xiaobo (Frontiers in Earth Science, 2022)
It is difficult to image the details of complex structures concealed around a horizontal hydraulic fracturing well using seismic data from the ground surface. In this paper, an approach is proposed to solve this problem by nonlinear full waveform inversion (FWI) using perforation seismic data. The feasibility of the approach was investigated using numerical modelling based on an experimental model built from the well-known SEG/EAGE overthrust model, which contains complex geological structures with faults. First, seismic modelling was performed to produce experimental synthetic data, including three sets of perforation seismic data recorded by different acquisition systems deployed in observation wells and on ground surface, and another set of conventional seismic reflection data with both sources and receivers deployed on the ground surface. Then, FWI was performed separately on each data set using an initial velocity model which was heavily smoothed to remove the target structures. The inversion results show that the concealed complex structures around the well were successfully recovered by the FWI using perforation data, while the benchmark image from the FWI using conventional seismic data was poor. Particularly, the experiments also demonstrated that FWI using perforation seismic data can image the faults around a horizontal hydraulic fracturing well, while this is unable to achieve using conventional ground surface seismic data. This conclusion was also proved to be valid for noisy data deteriorated either by synthetic Gaussian or field noises. Further experiments demonstrated that FWI using perforation data recorded from wells outperformed that of surface data in terms of structure imaging accuracy characterized by quantitative errors.